PENGARUH RETURN ON EQUITY, EARNING PER SHARE, CURENT RATIO, DEBT TO EQUITY RATIO TERHADAP HARGA SAHAM PADA PERUSAHAAN CONSUMER GOODS YANG TERDAFTAR DI BEI - Caroline, Caroline; Shellin, Shellin; Putri, Arie Pratania; Purba, Rahima Br (JURNAL LENTERA BISNIS, 2025)
The purpose of this research is to analyze the influence of ROE, EPS, CR, and DER on the stock prices of Consumer Goods companies listed on the Indonesia Stock Exchange (IDX). The sample used to support the continuity of the research dynamics is 12 companies listed on the IDX that meet the assessment requirements. The research hypothesis testing was conducted through the adoption of the IBM SPSS 25 for Windows program. In this study, the multiple linear test method was adopted, the classical assumption test, the normality test, the multicollinearity test, the heteroscedasticity test, the determinant coefficient, the T test, and the F test. The results prove that ROE and EPS partially have a significant negative effect on stock prices, and CR and DER have no effect on stock prices. The results of the simultaneous test show that ROE, EPS, CR, and DER have an effect on stock prices. The magnitude of the influence of the four variables on stock prices shows a result of 36% through the Adjusted R Square Value.